Towards Gender Equality in Agri-food System: Designing a Women's Empowerment Index in Integrated Farming Systems - Wulandari, Suci (National Research and Innovation Agency, Indonesia, 2023)
The Integrated Farming System (IFS) has been rapidly expanding in agri-food systems due to its potential for sustainable agriculture, increased productivity, income diversification and climate change adaptation aligning with market demands. However, women’s participation and contributions in IFS are hindered by gender norms, limited access to resources, low adoption of technology and unequal decision-making power. Currently, there is no existing measurement tool for women’s participation in IFS. The use of existing measurement tools is not applicable due to the complexity of IFS. It encompass the integration of diverse agricultural systems, including the Integrated Crop Livestock System and Mix Crops System, while also necessitating horizontal and vertical integration of business operations. This research aims to design the Women’s Empowerment Index in Integrated Farming Systems as a comprehensive tool for measuring women’s participation in agri-food system. The index aims to address gender gaps by evaluating women’s inclusion across various dimensions of IFS. The index considers dimensions such as: (a) access to resources, (b) decision-making power, (c) knowledge and skills, (d) entrepreneurial skill, (e) technology adoption, (f) income and economic empowerment, (g) social empowerment and well-being, and (h) sustainable practices and environmental management. The measurement is conducted using Multidimensional Scaling with weighting using the Analytical Hierarchy Process. By providing a comprehensive assessment of women’s empowerment, this index can reveal the status of women’s participation, inform policies and programs, and promote gender equality by recognizing and integrating women’s contributions and needs in the agri-food system.